Getting there from here: A literature review of VET reform implementation - Katherine Caves; Severin Baumann (ETH Zurich, KOF Swiss Economic Institute, 2018)
Despite huge incidence of vocational education and training (VET) reforms, we know more about good VET systems than how to implement them. In this review, we develop a determinant framework for VET implementation that combines theories and frameworks related to policy and general education reform, plus VET theory and the few existing VET implementation frameworks. We review 1,835 sources on VET reform implementation and code 177 for 1,538 framework-item mentions. Key success factors are employer, intermediary, and educator involvement; human, financial, and research resources; cooperation and coordination; clear strategy with political will and context fit; and accountability. There is a bias towards Europe, though it does not drive results. The sample equally represents developed and developing countries. Future research should test our framework, examine item interactions, and develop theory. VET reform implementation is distinct from general education reform implementation, and its evidence base is bigger than expected but less systematic than it should be.
Keywords: 330; VET; implementation; VET reform; reform implementation